Ship Manuvering Analysis Using Virtual Captive Model Test On Trim And Sinkage Variations - Audi Razif Santoso; Fakhri Akbar Ayub (Fakultas Teknik UPN Veteran Jakarta, 2026)
This study evaluates the effect of trim and sinkage variations on ship hydrodynamic characteristics using the Virtual Captive Model Test (VCMT) based on Computational Fluid Dynamics (CFD) for the KRISO Container Ship (KCS) model. Simulations were conducted for sinkage variations of −0.00090, −0.00275, and −0.00599 and trim variations of 0.017°, 0.053°, and 0.097°, over drift angles ranging from 2° to 10° under two speed conditions represented by Froude numbers 0.152 and 0.163. The objective is to investigate the influence of trim and sinkage on lateral force (sway) and yaw moment and to determine hydrodynamic coefficients using the Least Squares regression method. The results show that trim and sinkage influence sway force and yaw moment, although their effects are smaller than those of speed and drift angle. Increased sinkage generally produces higher sway force and yaw moment due to increased wetted surface area and changes in hull pressure distribution, while trim mainly alters the longitudinal pressure distribution with relatively limited influence within the investigated range. The maximum nondimensional values of Y′ and N′ were obtained at Fr = 0.163 and a drift angle of 10° (Y′H = 0.206543 and N′H = 0.079192 for sinkage variation; Y′H = 0.202338 and N′H = 0.073965 for trim variation). The hydrodynamic forces and moments were nondimensionalized using the Yoshimura–Masumoto formulation and analyzed through Least Squares regression, yielding coefficients that agree well with the simulation results. The VCMT-based CFD approach combined with Least Squares regression provides an effective alternative for determining ship maneuvering hydrodynamic coefficients.